Micromorphological analysis of glacial sediments in Antarctica: An example from the Ricker Hills tillite. - Fasano F; BARONI, CARLO (Terra Antartica Reports, 2003)
A number of sections of tillite and glacio-deformed bedrock have been collected at Ricker Hills (Victoria Land). The thin section have been analyzed and described with a micromorphological approach for characterizing the depositional environment.